DETERMINAN INTEGRATED REPORTING DISCLOSURE PADA PERUSAHAAN SEKTOR CONSUMERS NON-CYCLICALS TAHUN 2019-2021 - Velicia, Gabie; Imelda, Elsa (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to determine the impact of company size, growth opportunity, and company age as a determinant variable towards integrated reporting disclosure (IRD) on consumers non-cyclicals sector listed on the Indonesia Stock Exchange during 2019-2021. The sample was picked using a purposive sampling technique and 56 companies were used for this research. Data processing techniques using multiple regression and correlation analysis which assisted by EViews 12 for Windows and Microsoft Excel 2016. The results of this study indicate that firm size and firm age have positive significant influence and correlation on IRD. The implication of this research is that company should aim to increase the size of the company and maintain the sustainability of the company to increase the score of IRD. Because a high score of IRD reflects a good market value.